Communication and Partnering Strategies with Parents of Children with Early Childhood Special Needs: Strategi Komunikasi Dan Bermitra Dengan Orang Tua Yang Mempunyai Anak Berkebutuhan Khusus Usia Dini - Arifah Nurhadiyati; Angger Timansah; Imaratul Ulwiyah (Lembaga Riset dan Inovasi Masyarakat Madani, 2026)
Parents play a central role in supporting the development of young children with special needs. However, many parents experience emotional stress and limited understanding of appropriate educational and therapeutic services, which affects their acceptance of their children’s conditions. This community service activity was conducted in Sumbersari, Jember Regency, and involved 20 participants consisting of parents of young children with special needs and inclusive early childhood teachers. The activity aimed to enhance parents’ and teachers’ understanding of early intervention services and to strengthen parental acceptance through a communication and partnership-based approach. The methods included socialization, focused discussions, practical demonstrations, and evaluation. Data was collected using pre-test and post-test instruments in the form of checklists with a four-point Likert scale and analyzed descriptively by comparing mean scores. The results indicate an increase in the average scores of parents’ and teachers’ understanding as well as parental acceptance after the implementation of the activity. These findings suggest that socialization and collaborative communication approaches contribute positively to improving participants’ readiness to support early intervention services for children with special needs. This activity contributes as an initial model for strengthening parent–teacher partnerships in creating a more supportive and sustainable early childhood intervention environment.